Analysis of environmental factors in the adoption of iso/iec 29110. Multiple case study - Lucho Romero, Cesar Stuardo (Pontificia Universidad Católica del Perú, 2017)
The software industry comprising small companies represents an interesting opportunity for economic development. But these still have problems in productivity and the quality of their delivered products. In this context, the ISO/IEC 29110 standard has been developed, which represents an opportunity for small companies whose adoption depends on several factors, in particular, those related to the environment. In this paper, we study the influence of environmental factors on the adoption of ISO/IEC 29110 standard. For this research, a multiple case study was carried out, which includes four organizations as units of analysis. In a controlled environment, each organization implemented the processes belonging to the basic profile of the ISO/IEC 29110 standard. After the implementation, an analysis has been made of the environmental factors that influenced the adoption of the standard. Of the 16 environmental factors analyzed, it was found that 6 factors influenced all the organizations and those related to the support and trust of the partners had the greatest positive influence on the standard adoption, while the defense factor of the partners had the most negative influence. All other factors had minimal or no influence.
Keywords: Programas para computadoras--Desarrollo; Pequeñas empresas--Innovaciones tecnológicas; https://purl.org/pe-repo/ocde/ford#1.02.00